Respuesta :

Answer:

-6

Step-by-step explanation:

[tex]\text{Given that,}\\\\5x-4x^2 +3 \\\\\text{When}~ x = -1,\\\\~~~5(-1) -4(-1)^2 +3 \\\\=-5-4(1)+3\\\\=-5-4+3\\\\=-5-1\\\\=-6[/tex]

[tex] \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \huge\underline\mathfrak{\color{fuchsia} {AnSwer}}[/tex]

[tex]\: \: \: \: \: \: \: \: \: \: \:[/tex]

[tex]\tt{p(x)=5x-4x^2 + 3}[/tex]

[tex]\: \: \: \: \: \: \: \: \: \: \:[/tex]

On putting x= -1

[tex]\: \: \: \: \: \: \: \: \: \: \:[/tex]

[tex] \: \: \: \: \: \: \: \: \: \tt{p(-1)=5(-1)-4(-1)2+ 3}[/tex]

[tex] \: \: \: \: \: \: \: \: \: \: \: [/tex]

[tex]\: \: \: \: \: \: \: \: \:\tt{p(-1)=-5-4(1) +3}[/tex]

[tex]\: \: \: \: \: \: \: \: \: \: \:[/tex]

[tex]\: \: \: \: \: \: \: \: \:\tt{p(-1)=-5-4+3}[/tex]

[tex]\: \: \: \: \: \: \: \: \: \: \:[/tex]

[tex]\: \: \: \: \: \: \: \: \:\tt{p(-1)=-9+3}[/tex]

[tex]\: \: \: \: \: \: \: \: \: \: \:[/tex]

[tex]\: \: \: \: \: \: \: \: \:\tt{p(-1)=-6}[/tex]

ACCESS MORE

Otras preguntas